2013
DOI: 10.1364/ome.3.002022
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of transparent Y_3Al_5O_12: Eu ceramics

Abstract: Yttrium aluminum garnet transparent ceramics with divalent or trivalent europium ion doping were prepared by vacuum sintering at 1780 °C. Refined XRD data confirmed the pure phase ceramic with little lattice expansion. The transmittance of the 1.1 mm thick blue color divalent europium doped sample was measured to be 61% at wavelength of 900 nm. The photoluminescence spectrum exhibited the typical broad emission related to divalent europium ions. Furthermore, the photoluminescence spectra of the samples with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…It can be noticed that the cell parameters and cell volume increase with increase in the concentration ratio of activator/co-activators ions Eu x 2þ /Dy 0.10-x 3þ up to 0.03 (x ¼ 0.03) and decrease thereafter. 29 Such characteristics have been previously observed and discussed for other rare-earth oxide systems in our earlier publications. [24][25][26][27][28] This is occur due to the presence of access amount of activators/co-activators in host lattice, which creates lattice contraction effect.…”
supporting
confidence: 67%
“…It can be noticed that the cell parameters and cell volume increase with increase in the concentration ratio of activator/co-activators ions Eu x 2þ /Dy 0.10-x 3þ up to 0.03 (x ¼ 0.03) and decrease thereafter. 29 Such characteristics have been previously observed and discussed for other rare-earth oxide systems in our earlier publications. [24][25][26][27][28] This is occur due to the presence of access amount of activators/co-activators in host lattice, which creates lattice contraction effect.…”
supporting
confidence: 67%
“…We did not repeat this experiment because many authors already confirmed it. In the aluminum and gallium garnets (e.g., YAG) the emission due to 5 D0→ 7 F1 transition dominates the spectra because the Eu 3+ ion occupies a site that has an approximate center of symmetry [18]. In the Ca2NaMg2V3O12 garnet, the emission due to the 5 D0→ 7 F2 transition gives a higher intensity than the other Eu 3+ emissions in these V-garnets.…”
Section: Resultsmentioning
confidence: 99%
“…Probably, however, Eu 3+ is on both Ca 2+ /Na + and Mg 2+ sites at the same time [7]. The introduction of nitrogen into the structure further disturbs the symmetry around the Eu 3+ ion, which causes that the Eu 3+ emission from the sample obtained in the ammonia atmosphere is more intense than from the sample In the aluminum and gallium garnets (e.g., YAG) the emission due to 5 D 0 → 7 F 1 transition dominates the spectra because the Eu 3+ ion occupies a site that has an approximate center of symmetry [18]. In the Ca 2 NaMg 2 V 3 O 12 garnet, the emission due to the 5 D 0 → 7 F 2 transition gives a higher intensity than the other Eu 3+ emissions in these V-garnets.…”
Section: Resultsmentioning
confidence: 99%
“…Yttrium Aluminum Garnet, Y 3 Al 5 O 12 (YAG) has been the subject of intense research efforts because of their wide use as detectors, laser host materials and phosphors [1][2][3][4][5][6][7]. In particular, a great deal of research has been conducted on doping and co-doping YAG with transition metals like Ce, Nd, Eu, Dy, Yb, Cr to investigate their effects on its optical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Cerium-doped YAG (Ce: YAG) has received considerable attention because of its intense emission at 525 nm and its important role in converting blue emission to white light in InGaN light-emitting diodes [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%